2014
DOI: 10.1371/journal.pone.0114869
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine Treatment Delays Postnatal Motor Development and Blocks Short-Term Memory in Young Mice

Abstract: During the development of the nervous system, the perinatal period is particularly sensitive as neuronal connections are still forming in the brain of the neonate. Alpha2-adrenergic receptors are overexpressed temporarily in proliferative zones in the developing brain, reaching a peak during the first postnatal week of life. Both stimulation and blocking of these receptors during this period alter the development of neural circuits, affecting synaptic connectivity and neuronal responses. They even affect motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…Moreover, studies also demonstrated that exercise increases the expression of estrogen receptors alpha (ERα) that are found in skeletal muscle, including in mitochondria, which is associated with the increase in mitochondrial function. 22,56,57 In this way, estrogen may be potentially acting in cell signaling and stimulating the expression of Mn-SOD, or simply acting as an oxidant scavenger, due to its structural similarity to other antioxidants like vitamin E, 55 which can explain the reduced oxidant content and also the antioxidant network, found in the females in our model. Unfortunately, we did not evaluate the estrous cycle on females and the hormonal profile of the groups to answer this specific hypothesis in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, studies also demonstrated that exercise increases the expression of estrogen receptors alpha (ERα) that are found in skeletal muscle, including in mitochondria, which is associated with the increase in mitochondrial function. 22,56,57 In this way, estrogen may be potentially acting in cell signaling and stimulating the expression of Mn-SOD, or simply acting as an oxidant scavenger, due to its structural similarity to other antioxidants like vitamin E, 55 which can explain the reduced oxidant content and also the antioxidant network, found in the females in our model. Unfortunately, we did not evaluate the estrous cycle on females and the hormonal profile of the groups to answer this specific hypothesis in our study.…”
Section: Discussionmentioning
confidence: 94%
“…Muscle force in mice was measured in vivo using a Grip Strength Columbus apparatus (Cibertec SA) as indicated [39]. Behavior was analyzed by passive avoidance to test associative memory and other tasks such as hot-plate sensitivity, exploratory locomotor activity by the open field actimeter [40]. Associative short- and long-term memories were determined by novel object recognition (NOR) task as described [41].…”
Section: Methodsmentioning
confidence: 99%
“…Clonidine administration during P8–P21 (P8, 8 μg/kg; P9, 25 μg/kg, twice a day, subcutaneous, 100 μg/kg) reduced rapid eye movement sleep during P8–P21 and increased locomotor activity at the adult stage (>P70; Mirmiran et al, 1983 ). In mice, clonidine treatment during the P1–P22 period (daily, subcutaneous, 35 μg/kg) resulted in a temporal delay in the appearance of developmental markers (surface righting, cliff aversion, rooting, pinna detachment, startle response, eye twitch, eye opening), reduced exploratory locomotor activity at P16, and impaired short-term memory in the novel object recognition task at P22 ( Calvino-Núñez and Domínguez-del-Toro, 2014 ).…”
Section: De-regulated Neonatal Monoaminergic Signaling As a Possible ...mentioning
confidence: 99%